The endocrine role of hepatokines: implications for human health and disease - Iglesias, Pedro (Frontiers in Endocrinology, 2025)
The present narrative review analyzes the biology of hepatokines as well as their physiological functions and their effect on metabolism and different endocrine-metabolic diseases. Hepatokines are proteins secreted by the liver that play important roles in the regulation of energy homeostasis, inflammation and insulin resistance, behaving as relevant factors in the pathophysiology of pathologies such as obesity, non-alcoholic fatty liver disease (NAFLD) and type 2 diabetes. These include FGF21, fetuin-A, selenoprotein P, IGF-1, HGF, and ANGPTL family proteins. In addition, advances in therapies aimed at modulating the action of these proteins, such as FGF21 analogues and ANGPTL3 inhibitors, with good results in NASH resolution, improved insulin sensitivity and serum lipid reduction, are discussed. Molecular pathways related to hepatic signaling, including transcription factors and mechanisms regulating hepatic secretion, are also addressed, opening possibilities for innovative therapeutic strategies. Understanding hepatokines and their mechanisms promotes the development of personalized treatments for metabolic diseases, contributing to improve metabolic health and prevent related complications. This review highlights the importance of integrating liver biology with the clinic to address current challenges in the management of metabolic diseases.